KETERAMPILAN PROSES SAINS SISWA SEKOLAH DASAR DALAM PEMBELAJARAN IPAS: TINJAUAN LITERATUR - Oktavera Rachmadita; Yuyu Yuliati; Dede Salim Nahdi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Science Process Skills (SPS) are essential competencies that support elementary school students in understanding Integrated Science and Social Studies (IPAS) concepts through scientific activities. However, previous studies indicate that students’ science process skills have not yet developed optimally. This study aimed to analyze the condition of elementary school students’ science process skills, identify the most dominant and least developed indicators, and examine effective learning models for improving science process skills in IPAS learning. The study employed a Systematic Literature Review (SLR) method guided by the PRISMA 2020 framework. Literature was collected from Google Scholar and Scopus databases using the Publish or Perish application, covering publications from 2017 to 2025. Of the 415 articles identified, 15 met the inclusion criteria and were analyzed. The findings revealed that students’ science process skills generally ranged from low to moderate levels. The most dominant indicators were observing, communicating, and classifying, while predicting, formulating hypotheses, and designing experiments were the least developed. Furthermore, inquiry and guided inquiry learning models were found to be the most effective approaches for enhancing students’ science process skills. These findings highlight the importance of student-centered and inquiry-based learning in developing science process skills within IPAS instruction.